Clinical, Hematological and Some Biochemical Parameters with Serum Cobalt and Vitamin B12 Levels in Cattle with Tropical Theileriosis - Issi, Mustafa; Gul, Yusuf; Basbug, Onur; Sahin, Nurhan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
It was aimed to determine some clinical, hematological and biochemical parameters along with serum cobalt and B-12 vitamin levels in cattle with tropical theileriosis. A total of 20 cattle including 10 clinically healthy cattle (control group) and 10 cattle with tropical theileriosis (patient group) were used as materials. While body temperature, respiratory frequency, total bilirubin (P<0.001). aspartate amino transaminase (AST), alanine amino transaminase (ALT), alkaline phosphatase (ALP) (P<0.01), heart frequency and B-12 vitamin levels (P<0.05) were increased in patient group compared with control group, rumen motility. hemoglobin amount, hematocrit value, total leukocyte number (P<0.001). erythrocyte number (P<0.01) and serum cobalt amount (P<0.05) were decreased in patient group compared with control group. In conclusion, it was determined that serum cobalt levels low, however B-12 vitamin levels high in cows with tropical theileriosis.
Tropikal theileriozisli sı?ırlarda klinik, hematolojik ve bazı biyokimyasal parametreler ile serum kobalt ve B12 vitamin düzeyleri
Keywords: Cattle; Tropical theileriosis; Vitamin B-12; Cobalt